Evaluation of the Relationship Changes between the Subjective Well-Being and Prosocial Actions - 2003*-2013 - Desjardins, Daniel (Université d'Ottawa | University of Ottawa, 2017)
In this paper, I provide empirical evidence of the positive association between the subjective well-being (SWB) of individuals and acting in a prosocial manner using the 2013 and 2003 large-scale Canadian data sets obtained from the General Social Survey (GSS) Cycle 17 and GSS Cycle 22. Using the ordinary least squares method for estimating the unknown parameters the results suggest that the association between acting in a prosocial way and one's self-rated life satisfaction has decreased between 2003 and 2013 and thus indicating a shift away from acting in a prosocial way as an approach to achieving greater subjective well-being.